Salt stress tolerance in cowpea is poorly related to the ability to cope with oxidative stress - Praxedes, Sidney Carlos; DaMatta, Fábio Murillo; Lacerda, Claudivan Feitosa de; Prisco, José Tarquinio; Gomes-Filho, Enéas (Acta Botanica Croatica, 2014)
We have previously demonstrated that salt tolerance in cowpea could be associated with lesser impairments of the photosynthetic capacity. Taking into account that photosynthesis is the main sink for reducing power consumption, our central working hypothesis is that a salt- sensitive cultivar is more prone to suffer from oxidative stress. We analyzed the long-term effects of salt stress on oxidative damage and protection against reactive oxygen species in both leaves and roots of a salt-tolerant (Pitiúba) and a salt-sensitive (TVu) cowpea cultivar. Two salt treatments (0 and 75 mM NaCl) were applied to 10-day-old plants grown in nutrient solution for 24 days. Significant salt-induced oxidative damage as demonstrated via increases in malondialdehyde concentration were noted, particularly in leaves at the end of the experiment, although such damage was found earlier in Pitiúba. In salt-stressed plants, superoxide dismutase (SOD) activity increased only in Pitiúba at 24 days from the start of salt additions (DSSA). In Pitiúba, catalase (CAT) was not significantly affected by the treatments, whereas in TVu its activity was dramatically lower in salt- tressed plants at 10DSSAonwards. In general salt stress led to significant increases, much more pronounced in ascorbate peroxidase (APX), glutathione reductase (GR) and guaiacol peroxidase (GPX), at the end of the experiment in both cultivars. In roots, salt-induced increases in enzyme activities were particularly noted at 24 DSSA, as found for SOD and APX in Pitiúba, CAT in TVu and GR and GPX in both cultivars. Therefore, in contrast to our expectations, the present results argue, to a great extent, against a functional link between salt stress tolerance and the expression of the antioxidant system. We also demonstrated that leaves and roots should be evaluated for a full assessment of whole plant acclimation to salt stress.